Arabic sociolinguistics : topics in diglossia, gender. identity, and politics - Bassiouney, Reem, 1973- (Georgetown University Press, 2020)
"This is a second edition of Arabic Sociolinguistics, a well-regarded book on the sociolinguistics of Arabic that was published in 2009. It is a copub with Edinburgh University Press. Along with general updates for the entire book, more substantive changes include: * New chapter on critical sociolinguistics, a new subfield * Restructuring and expansion of chapters 1 and 2 * New sections on language variation and media and performance in chapter 3 * New sections on language policies in the Arab World, as well as the impact to language that political changes in the Middle East have had Bassiouney is a former GU professor and previous editor of Al-'Arabiyya"--